Prognostic significance of the systemic immune-inflammation index in patients with extranodal natural killer/T-cell lymphoma - Hai, Tao; Wu, Wanchun; Ren, Kexin; Li, Na; Zou, Liqun (Frontiers in Oncology, 2023)
The systemic immune-inflammation index (SII) is based on the neutrophil, platelet, and lymphocyte counts, and has been identified as a prognostic marker in multiple types of cancer. However, the potential value of the SII for predicting survival outcomes in patients with extranodal natural killer/T-cell lymphoma (ENKTCL) has not been investigated thus far. Method: This study included 382 patients with ENKTCL treated with asparaginase-base regimens from 2021-2017 in West China Hospital (Chengdu, China). Clinical and demographic variables, as well as the prognostic value of the SII, were analyzed using Cox proportional hazards regression analysis. Results: The complete and objective response rates were 55.8% and 74.9%, respectively. Patients with high SII were associated with a lower rate of complete response, higher rate of B symptoms, and serum lactate dehydrogenase levels above or equal to the upper limits of normal (p < 0.01). Patients with low SII were linked to better overall survival and progressionfree survival than those with high SII (p < 0.01). Patients with early-stage disease or prognostic model for natural killer lymphoma with Epstein-Barr virus, defined as the low-risk group, could be further stratified according to the SII (p < 0.01). Negative prognostic factors were determined using the Cox proportional hazards regression analysis, which identified four variables: Eastern Cooperative Oncology Group performance status score ≥2; Stage III/IV disease; positivity for Epstein-Barr virus DNA in plasma; and high SII. Predictive nomograms for the prediction of 3-and 5-year overall survival, as well as progression-free survival, were constructed based on those four variables. The nomograms demonstrated favorable discriminating power.The SII is a novel prognostic marker for ENKTCL, which may be used for the prediction of poorer survival in low-risk patients.